A busca de Deus pela vontade e a vida cristã : ação moral e política no pensamento de Santo Agostinho - Fernandes, Nelson Luís de Carvalho (2023)
The work aims to address the foundation of human action, on the moral level within the thought of St. Augustine. It demonstrates that it is through the faculty of the will that any and all human action is carried out, since for Saint Augustine all action is nothing more than a will and, as such, through it, through the will, one also seeks God. To seek God through the movement of the will is to seek beatitude, therefore all the moral action of the Christian man has beatitude as its end and with it the enjoy- ment of God, which will be an act of charity. Therefore, the aim of Augustinian moral- ity is that man acts in such a way that he enjoys only charity and everything else is used in terms of the only object of full delight of man, which is God. The work will demonstrate that it is due to the misuse of the faculty of the will, which is free and good, that man is responsible for his misfortune and unhappiness. However, it will be through this same faculty that man will reach his beatitude. Such an act will require man's free choice, by his will moved by the weight of love, to submit and collaborate with the order established by God when he was created ex nihilo. By the act of his free choice alone, man cannot save himself. He needs and needs God's help, the gift of grace. Grace is a gift that God grants not to prevent man from sinning, but to help his will to desire good and to achieve it, that is, grace makes the will good and makes it want to do good by doing what is good. instead of evil, this is true freedom. This im- plies that all our moral action must be directed towards the Supreme Good and not towards the things that He created, these must only be used with a view to the Su- preme Good, and that is acting virtuously. The vicious moral action is directed to- wards the creature far from the highest Good. And that, according to our author's thought, is to sin and as such the action is said to be vicious. Therefore, it is by the will that we will merit bliss or eternal punishment.